B-type natriuretic peptide level in the diagnosis of asymptomatic diastolic dysfunction - Karaca, Ilgin; Guelcue, Erden; Yavuzkir, Mustafa; Dagli, Necati; Ilkay, Erdogan; Oezbay, Yilmaz; Arslan, Nadi (Turkish Soc Cardiology, 2007)
Objective: Brain natriuretic peptide (BNP) reflects the left ventricular pressure and volume overload. It is known that it increases in systolic dysfunction proportionally with left ventricular pressure increase. The BNP levels are well correlated with NYHA classification and prognosis. Our aim was to evaluate the predictive value of BNP in patients with diastolic dysfunction but normal systolic dysfunction demonstrated by echocardiography. Methods: Fifty patients (mean age: 48.5 +/- 6.75 years; 29 males, 21 females) were included in this cross-sectional, case-controlled study. Systolic dysfunction was the exclusion criterion. The following parameters were used to evaluate diastolic function: isovolumetric relaxation time, transmitral early to late filling flow velocities (E/A) ratio, deceleration time E, pulmonary vein Doppler findings and color mitral flow propagation velocity. Diastolic dysfunction was determined in 30 hypertensive patients (Group 1), whereas 20 patients who had normal diastolic flow patterns on echocardiography (Group 2). Blood samples were taken for serum BNP level measurements. Results: The BNP levels were 12.0 +/- 4.97 pg/ml in individuals with normal filling pattern and 66.17 +/- 17.56 pg/ml in individuals with abnormal filling patterns (p<0.001). The accuracy of BNP in detection of diastolic dysfunction was assessed with receiver-operating characteristic (ROC) analysis. The area under the ROC curve for BNP test accuracy in detection any abnormal diastolic dysfunction was 0.969 (95% CI, 0.909 to 1.029; p<0.001). A BNP value of 37.0 pg/ml had sensitivity of 80%, specificity of 100%, a positive predictive value of 100%, a negative predictive value of 23% and accuracy of 88% in identifying asymptomatic prolonged relaxation pattern. We found a strong correlation between left ventricular mass index and plasma BNP levels (r=0.62, p<0.05). Conclusion: Estimation of BNP values could be accepted as a fast and reliable blood test in the diagnosis of asymptomatic diastolic dysfunction.
Keywords: B-type natriuretic peptide; diastolic dysfunction; hypertension